“Disabled People Are Sexual Citizens Too”: Supporting Sexual Identity, Well-being, and Safety for Disabled Young People - Shah, Sonali (Frontiers in Education, 2017)
Disabled young people are sexual beings, and deserve equal rights and opportunities to have control over, choices about and access to their sexuality, sexual expression and fulfilling relationships throughout their lives. This is critical to their overall physical, emotional and social health and wellbeing. However, societal misconceptions of disabled bodies being non-normative, Other or deviant has somewhat shaped how the sexuality of disabled people has been constructed as problematic under the public gaze. The pervasive belief that disabled people are asexual creates barriers to sexual citizenship for disabled young people, causing them to have lower levels of sexual knowledge and inadequate sex education compared to their non-disabled peers. As a consequence they are more vulnerable to ‘bad sex’ - relationships which are considered to be exploitative and disempowering in different ways. Access to good sex and relationships education (SRE) for disabled young people is, therefore, not only important for them to learn about sexual rights, sexual identity and sexual expression, but also about how to ensure their sexual safety. In so doing it will contribute to the empowerment and societal recognition of disabled people as sexual beings, and also help them resist and report sexual violence. Therefore, it is critical that parents, educationalists and health and social care professionals are aware and appropriately equipped with knowledge and resources to formally educate disabled young people about sexuality and wellbeing on par to their non-disabled peers.